Development and Validation of a Novel Second Derivative UV Method for the Estimation of Antihypertensive Drugs in Tablet Dosage Form - Zambrekar, Sonal; Sawaikar, Leena; Keny, Swati; Pal, Pradnya; Gaude, Surashree (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim The objective of the current work was to develop and statistically validate a second order derivative method for estimating atenolol in tablet dosage form using UV spectrophotometry. Materials and Methods The method validation was done in accordance with ICH recommendations. Atenolol (BSC class III) and hydrochloride (BSC class II) were soluble in 0.1 N NaOH and gave stable absorbance with it, hence 0.1 N NaOH was chosen as a solvent. The wavelengths selected were 226 nm and 274 nm for atenolol and hydrochlorothiazide respectively. The proposed method was validated for parameters like linearity, precision, robustness, accuracy, limit of detection and limit of quantification. Results The method was found to be linear with a correlation coefficient (R2) of 0.999 and within a concentration range of 5-60 μg/mL for atenolol and 5-50 μg/mL for hydrochlorothiazide. The analysis of tablet formulation was carried out using second order derivative method and percentage mean assay was found to be 100.4% and 100.9% for atenolol and hydrochlorothiazide respectively. The method was statistically validated showed less % RSD indicating that method is precise, accurate and robust.
Keywords: Atenolol; Hydrochlorthiazide; UV spectroscopy; Second derivative; ICH guidelines